THE HISTORICAL DEVELOPMENT OF NEOLOGISM STUDIES: FROM TRADITIONAL APPROACHES TO MODERN LINGUISTIC TRENDS - Shakhzod Akhmedov; Badar Al Mamari; Faedurrohman; Muhammad Syaifullah; Eva Lathifah Fauzia; Muhammad Nur Iman (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study examines the historical development of neologism studies through a historical-analytical approach that traces the movement from early descriptive and lexicographic observations to structural, generative, sociolinguistic, cognitive, and computational perspectives. Drawing on a purposive sample of classical and modern linguistic sources, the paper analyzes how the concept of neologism, its mechanisms of formation, and its diffusion have been understood across different stages of linguistic scholarship. The study argues that neologisms should not be treated merely as isolated new lexical items, but as indicators of broader processes of lexical change shaped by cultural, social, and technological transformation. The findings show that the study of neologisms has become increasingly interdisciplinary and that a comprehensive understanding of lexical innovation requires integrating historical, social, and digital perspectives.